Cordyceps cateniannulata and Cordyceps javanica: first report of pathogenicity to Glycaspis brimblecombei (Hemiptera: Aphalaridae) - Domingues, Maurício Magalhães [UNESP]; Santos, Paula L. [UNESP]; Gêa, Bianca C. C. [UNESP]; Carvalho, Vanessa R. [UNESP]; Oliveira, Fabricio N. [UNESP]; Soliman, Everton P.; Pereira, Fabricio F.; Zanuncio, José C.; Wilcken, Carlos Frederico [UNESP] (My University, 2022)
Cultivation of species of the genus Eucalyptus is important for the Brazilian economy, with 6.97 million hectares planted. Glycaspis brimblecombei Moore (Hemiptera: Aphalaridae), detected in Brazil in 2003, has dispersed and now damages Eucalyptus crops in all regions of this country. The location and identification of entomopathogenic fungi isolates may increase the options for integrated pest management. The objective of this research was to evaluate the pathogenicity of Cordyceps cateniannulata and Cordyceps javanica isolates to G. brimblecombei. Ten nymphs of G. brimblecombei, with or without lerps, were placed per Eucalyptus leaf cut with one of its edges on hydroretentive gel inside Petri dishes. The fungi isolates were suspended in a solution of Tween 80 (0.1%) at the concentration of 1.0 x 108 conidia mL-1 and sprayed on the G. brimblecombei nymphs. The mortality of this insect was evaluated daily for seven days, and the dead individuals were transferred to humid chambers. The conidia viability of the isolates was greater than 93%. The mortality of G. brimblecombei nymphs, seven days after the application of the fungi, was 100%. This is the first report of the pathogenicity of C. cateniannulata and C. javanica isolates, occurring naturally in the field, to G. brimblecombei.
Keywords: biological control; entomopathogenic fungi; Eucalyptus; pest management